SPATIAL CLUSTERING-BASED GAS STATION LOCATION DETERMINATION - Ayasda Rahardian; Eneng Tita Tosida; Ema Kurnia; Hairulnizam Mahdin (International Journal of Quantitative Research and Modeling, 2023)
The absence of gas stations built in Cibeber Subdistrict is not balanced with the high level of transportation use for ease of mobility among residents. The purpose of this research is to cluster data using K-Means clustering and spatial modeling to provide a potential location for the construction of gas stations in Cibeber District. Based on the research process that has been carried out using RStudio, the potential villages for the construction of gas stations consist of four villages, namely Cikotok, Cibeber, Neglasari, and Wanasari. As for the results of spatial modeling, Cibeber District has a total of 862 potential location points, and within the scope of potential villages, namely four villages, there are 233 potential location points. Then, after being processed with weighted products for optimization and getting the best location results, 3 potential locations were obtained, namely Tegalumbu Village located in Wanasari Village, Nagrak Village located in Cikotok Village, and Cinangga Village located in Cibeber Village.